2008
DOI: 10.1210/me.2007-0460
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Group Box Proteins Modulate Tumor Necrosis Factor-α Expression in Osteoclastogenesis via a Novel Deoxyribonucleic Acid Sequence

Abstract: We have previously shown that mice lacking the TSH receptor (TSHR) exhibit osteoporosis due to enhanced osteoclast formation. The fact that this enhancement is not observed in double-null mice of TSHR and TNFalpha suggests that TNFalpha overexpression in osteoclast progenitors (macrophages) may be involved. It is unknown how TNFalpha expression is regulated in osteoclastogenesis. Here, we describe a receptor activator for nuclear factor-kappaB ligand (RANKL)-responsive sequence (CCG AGA CAG AGG TGT AGG GCC), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…Recently, we have shown that suppression of HO-1 by pharmacological and genetic inhibition causes enhanced HMGB1 release during osteoclastogenesis (7). Extracellular HMGB1, which acts as a proinflammatory cytokine, can bind to cell-surface receptors such as the receptor for advanced glycation end products and Toll-like receptors 2 and 4 and modulates differentiation of OCL precursors in the presence of RANKL in vitro and in vivo (23,29,30). In this study, kahweol induced up-regulation of HO-1 and inhibited extracellular release of HMGB1 during osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, we have shown that suppression of HO-1 by pharmacological and genetic inhibition causes enhanced HMGB1 release during osteoclastogenesis (7). Extracellular HMGB1, which acts as a proinflammatory cytokine, can bind to cell-surface receptors such as the receptor for advanced glycation end products and Toll-like receptors 2 and 4 and modulates differentiation of OCL precursors in the presence of RANKL in vitro and in vivo (23,29,30). In this study, kahweol induced up-regulation of HO-1 and inhibited extracellular release of HMGB1 during osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 50%
“…Another important issue is that periodontium also contains hard tissues: cementum and alveolar bone. Yamoah et al (32) have reported an interrelationship between HMGB1, TNF-α expression and osteoclast formation. A thorough understanding of the molecular mechanism of HMGB1 and its effects on various local cells is essential before this molecule can be applied clinically.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of TSH on TNFα synthesis is mediated transcriptionally by binding of two high mobility group box proteins, HMGB1 and HMGB2, to TNFα gene promoter [75]. TNFα production is expectedly upregulated in osteoporotic TSHR -/-mice [37], and the genetic deletion of TNFα in these mice reverses the osteoporosis, as well as the bone formation and resorption defects, proving that the TSHR -/-phenotype is mediated by TNFα, at least in part [64,76].…”
Section: Mechanism Of Actionmentioning
confidence: 99%